Bio-inspired microcapsule for targeted antithrombotic drug delivery. Issue 48 (31st July 2018) - Ye, Wei; Wang, Nan; Hu, Kebang; Zhang, Lincai; Liu, Aihui; Pan, Changjiang; Gong, Tao; Liu, Tao; Ding, Hongyan
Abstract : NK-loaded hollow microcapsules were fabricated and assessed as a potential antithrombosis therapy. Abstract : Thrombosis or embolism is the leading cause of death and long-term adult disability worldwide. To reduce the risk of thrombosis and hemorrhaging in patients, a facile and versatile method was developed to fabricate microcapsules for targeted antithrombotic drug delivery. The microcapsules were prepared via oxidative polymerization of dopamine on polystyrene microspheres, followed by immobilization of fibrinogen onto the surface of poly(dopamine) layers. Subsequently, microcapsules were obtained by removing the cores with THF. Nattokinase was loaded into the microcapsules via diffusion. The loading amount was approximately 0.05 mg g −1 at 37 °C, and the loading efficiency was nearly 75%, based on the initial concentration of nattokinase in PBS. The release of nattokinase was a gradual process at 37 °C, and the activity of the targeted activated platelets was highly efficient. The antithrombotic activity of the nattokinase microcapsules was evidenced by the sharp dissolution of fibrin clots and the blood clotting time indexes. A gradual release mechanism of platelet-inspired microcapsules used for targeted antithrombotic therapy was proposed. This strategy for targeted antithrombotic drug delivery, which lowers the demand dose and minimizes side effects while maximizing drug efficacy, provides a potential new way to treat life-threatening diseases caused by vascular disruption.